Glycoprotein targeted therapeutics: a new era of anti‐herpes simplex virus‐1 therapeutics. (26th February 2013) - Antoine, Thessicar E.; Park, Paul J.; Shukla, Deepak
SUMMARY Herpes simplex virus type‐1 (HSV‐1) is among the most common human pathogens worldwide. Its entry into host cells is an intricate process that relies heavily on the ability of the viral glycoproteins to bind host cellular proteins and to efficiently mediate fusion of the virus envelope with the cell membrane. Acquisition of HSV‐1 results in a lifelong latent infection. Because of the cycles of reactivation from a latent state, much emphasis has been placed on the management of infection through the use of DNA synthesis inhibitors. However, new methods are needed to provide more effective treatment at earlier phases of the viral infection and to prevent the development of drug resistance by the virus. This review outlines the infection process and the common therapeutics currently used against the fundamental stages of HSV‐1 replication and fusion. The remainder of this article will focus on a new approach for HSV‐1 infection control and management, the concept of glycoprotein‐receptor targeting. Copyright © 2013 John Wiley & Sons, Ltd.